Capital Intensity, Tanggung Jawab Sosial Perusahaan, Dan Tax Aggeressiveness: Good Corporate Governance Sebagai Variabel Moderasi - Muhammad Agung S (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: This study aims to examine the effect of capital intensity and corporate social responsibility on tax aggressiveness with good corporate governance as a moderating variable. Method: This study uses samples obtained from manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020, using a purposive sampling method with a sample of 40 companies with 142 annual financial statements. The method used in this research is multiple regression analysis and absolute difference value test. Finding: The results of this study indicate that capital intensity has a negative effect on tax aggressiveness. Corporate social responsibility has no effect on tax aggressiveness. Good corporate governance is able to moderate capital intensity on tax aggressiveness. Good corporate governance is not able to moderate corporate social responsibility towards tax aggressiveness. Novelty: The researchers added a moderating variable of good corporate governance, because it has a considerable influence in overseeing the performance of management to run the company's operations and to see how much influence good corporate governance has moderated in the study.